The use of the be-passive in academic Englishes: local versus global usage in an international language. Issue 1 (April 2016) - Hundt, Marianne; Schneider, Gerold; Seoane, Elena
Abstract : In this paper, we examine the diffusion of a syntactic change in a specialised text type in different World Englishes – in particular, the use of be -passives in academic discourse in nine contact varieties of English and six English as a Native Language (ENL) varieties. The Zürich-parsed International Corpus of English (ICE) makes it possible to retrieve automatically, for the first time, the two variants in the envelope of variation: active transitive constructions and be -passives. We apply regression analysis in order to gauge the effect of potential external factors that play a role in the choice between them: regional variety (with potential influence from the substrate in the contact varieties) and academic sub-discipline. The use of the passive has undergone change in the twentieth century (see, for example, Leech et al ., 2009 ). As a necessary backdrop for variation found in the ICE corpora, we therefore use historical data from the extended Brown family of corpora, which have also been parsed at the University of Zürich. The results of our analysis show that regional variety is less important than academic sub-discipline: with the sole exception of American English, be -passives are about equally frequent in both ENL and contact varieties; moreover, they are distributed similarly across all varieties according to academic sub-discipline (humanities, social sciences, natural sciences and technology).